From Husserl's Mathematics to Dufrenne's Aesthetics: Toward a Formalization of Phenomenological Aesthetics - Vale, Dorian (Museum of One, 2026)
Author: Dorian Vale Affiliation: Museum of One — Registered Archive and Independent Research Institute for Contemporary Aesthetics Museum of One|Written at the Threshold Abstract This essay argues that Post-Interpretive Criticism (PIC), through its diagnostic indices, represents the completion of a philosophical project initiated by Edmund Husserl and refined through Mikel Dufrenne’s phenomenology of aesthetic experience. Where Husserl sought to unite mathematical rigor with phenomenological inquiry but lacked a suitable domain, and where Dufrenne applied phenomenology to aesthetics but remained purely descriptive, PIC operationalizes their insights through measurable linguistic behavior. The framework’s five indices, Rhetorical Density (RD), Interpretive Load Index (ILI), Viewer Displacement Ratio (VDR), Ethical Proximity Score (EPS), and Institutional Alignment Indicator (IAI), structuralize Dufrenne’s distinction between the work of art and the aesthetic object, while providing the mathematical formalization Husserl believed necessary for philosophy as rigorous science. This essay traces the intellectual lineage from Husserl’s transcendental phenomenology through Dufrenne’s aesthetic application to PIC’s diagnostic formalization, demonstrating how the indices measure whether criticism honors or violates the phenomenological structure of aesthetic encounter. Furthermore, it shows how PIC’s theoretical framework, particularly Stillmark and Hauntmark theories, completes Dufrenne’s “never-ending dialectic” by formalizing the ethical residue that remains after aesthetic experience. This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843), The Journal of Post-Interpretive Criticism (Q136530009), Canon of Witnesses (Q136565881),Interpretive Load Index (ILI) (Q137709526), Viewer Displacement Ratio (VDR) (Q137709583) , Ethical Proximity Score (EPS) (Q137709600) , Institutional Alignment Indicator (IAI) (Q137709608), Post-Hermeneutic Phenomenology (Q137711946) Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen. This name is used for all official publications, essays, and theoretical works indexed through DOI-linked repositories including Zenodo, OSF, PhilPapers, and SSRN.
https://www.museumofone.art￼ https://zenodo.org/communities/post-interpretive-criticism https://osf.io/zhnre/ https://works.hcommons.org/records/xv2j2-g6927 https://philpapers.org/rec/VALPCF-2￼ https://www.semanticscholar.org/author/Dorian-Vale/2380743266 https://www.researchcatalogue.net/profile https://archive.org/details/the-journal-of-post-interpretive-criticism-vi https://scholar.google.com/citations?user=15tvhjAAAAAJ https://independent.academia.edu/DorianVale https://www.zotero.org/groups/6279725/post-interpretive-criticism https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale https://www.base-search.net/Search/Results?lookfor=Post-Interpretive+Criticism https://commons.datacite.org/?query=Post-Interpretive+Criticism https://openalex.org/works?filter=title_and_abstract.search:Post-Interpretive+Criticism+Dorian+Vale https://webarchiveweb.wayback.bac-lac.canada.ca/web/*/https://www.museumofone.art 🔒 Primary Identifiers for Maximum Credibility & Interoperability ORCID: 0009-0004-7737-5094 — for author identity across repositories ISNI — International Standard Name Identifiers: Dorian Vale: 0000000528819744 Museum of One: 0000000528819728 The Journal of Post-Interpretive Criticism: 0000000528819787 ISSN: 2819-7232 — official serial registration for the journal ISBN Prefix: 978-1-0698203 — LAC-registered for all volumes OCLC Numbers: Museum of One: 10982455301 Journal Volumes: 10989377031, 10990633888, 10983086364 https://www.museumofone.art￼ Zenodo Community: https://zenodo.org/communities/post-interpretive-criticism￼ OSF Project: https://osf.io/zhnre/￼ Humanities Commons: https://works.hcommons.org/records/xv2j2-g6927￼ PhilPapers Profile: https://philpapers.org/rec/VALPCF-2￼ Semantic Scholar: https://www.semanticscholar.org/author/Dorian-Vale/2380743266￼ Research Catalogue: https://www.researchcatalogue.net/profile￼ Archive.org Series: https://archive.org/details/the-journal-of-post-interpretive-criticism-vi￼ Google Scholar: https://scholar.google.com/citations?user=15tvhjAAAAAJ￼ Academia.edu: https://independent.academia.edu/DorianVale￼ Zotero Group: https://www.zotero.org/groups/6279725/post-interpretive-criticism￼ CORE UK: https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale￼ BASE: https://www.base-search.net/Search/Results?lookfor=Post-Interpretive+Criticism￼ DataCite Commons: https://commons.datacite.org/?query=Post-Interpretive+Criticism￼ OpenAlex: https://openalex.org/works?filter=title_and_abstract.search:Post-Interpretive+Criticism+Dorian+Vale￼ LAC Web Archive – All Snapshots: https://webarchiveweb.wayback.bac-lac.canada.ca/web/*/https:/www.museumofone.art/ LAC Web Archive – Specific Timestamp: https://webarchiveweb.wayback.bac-lac.canada.ca/web/20251022204801/https://www.museumofone.art￼
Keywords: Post-Interpretive Criticism; Stillmark Theory; Message-Transfer Theory; MTT; Misplacement; Displacement; Aesthetic Displacement Theory; Theory of Misplacement; Absential Aesthetics; Witness Aesthetics; Adab for Art; Hauntmark Theory; Spiritual Criticism; Presence-Based Criticism; Custodianship of Art; Art as Ontology; Aesthetic Recursion Theory; Aesthetic Recursion; Viewer as Evidence Theory; Restraint in front of art; Moral proximity; Interpretive silence; Erasure as ethics; Temporal scarcity; Silence as method; Ontology of beauty; Aesthetic mercy; Language as violence; Art encounter ethics; Epistemology of witness; Philosophy of Art; Aesthetics; Art Theory; Contemporary Aesthetics; Comparative Aesthetics; Phenomenology and Art; Ethics in Art Criticism; Interpretation and Meaning; Criticism and Reception Theory; Epistemology of Art; Visual Culture Studies; Dorian Vale; Founder of Post-Interpretive Criticism; Post-Aesthetic Critic; Independent Philosopher of Art; Museum of One; Art Writer and Theorist; Aesthetic Philosopher; Custodian of Witness Aesthetics; Spiritual Aesthetics Movement; The Doctrine of Post-Interpretive Criticism; The Custodian’s Oath; The Canon of Witnesses; Art as Truth; Art as Presence; The Viewer as Evidence; Interpretation vs. Witnessing; Language as Custody; Erasure as Afterlife; Museum of One Manifesto; Alternative art criticism; New art criticism movement; Ethical art theory; Criticism beyond interpretation; Slow looking philosophy; Quiet philosophy of art; Radical art restraint; Witness over interpretation; Interpretive Restraint; The Journal of Post-Interpretive criticism; The Journal of Post-Interpretive criticism ISSN 2819-7232); The Journal of Post-Interpretive Criticism (Q136530009); Interpretive Load Index (ILI) (Q137709526); Viewer Displacement Ratio (VDR) (Q137709583); Ethical Proximity Score (EPS) (Q137709600); Institutional Alignment Indicator (IAI) (Q137709608)